Evaluation of 3D printing as an alternative method in the production of gas regulator parts (AACINI - International Journal of Industrial Engineering, 2021)
The aim of this research is to study alternative manufacturing processes for certain components of industrial gas regulators including a feasibility and rentability analysis. In particular, additive manufacturing will be studied as a non-conventional substitute to traditional component manufacturing, taking into account the component´s design, the apparatus and polymeric materials to be used. Firstly, materials selection criteria and characterization tests were determined. Additionally, evaluation of 3D printing methodologies and postproduction processes were conducted to assure that the 3D printed component will withstand the combined loads at which it will be exposed during normal operation. Also, the surface roughness requirements were considered when analyzing the material and the 3D printing method.In second place, an analysis of the impact of this change in the productive line and the gas regulator production will be conducted. Operative, logistic and economic issues will be contemplated to determine the feasibility and benefits of the modification of the process and the implementation of additive manufacturing in other industries.
Keywords: gas regulators; 3D printing; combined forces; polymeric materials; materials testing